2021
DOI: 10.23917/jramathedu.v6i2.12667
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy in creativity and curiosity as predicting creative emotions

Abstract: Self-efficacy constructs could predict students’ practices and affect in learning the sciences. Researchers have pointed at such constructs as predictors of students’ mathematics achievement and performance. Self-efficacy was also studied as predictor of emotions in learning mathematics, though little research has done so regarding self-efficacy as predictor of creative emotions. Another predictor of creative emotions could be curiosity. The present study has a regression-based modelling design, where it exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…A high response rate appeared with creativity'. This, in turn, confirms that curiosity triggers creativity [42], while obedience and conformity suppress it. Question six referred to the proposed process that was discussed and adopted at the outset as a classroom formula: "Do you agree with the statement: "A learning process based on presenting 'how to learn', proposing a topic, choosing a topic, orientating to the topic, conceptualising, exploring, experimenting, drawing conclusions, reflecting and describing one's own work has a number of benefits."…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…A high response rate appeared with creativity'. This, in turn, confirms that curiosity triggers creativity [42], while obedience and conformity suppress it. Question six referred to the proposed process that was discussed and adopted at the outset as a classroom formula: "Do you agree with the statement: "A learning process based on presenting 'how to learn', proposing a topic, choosing a topic, orientating to the topic, conceptualising, exploring, experimenting, drawing conclusions, reflecting and describing one's own work has a number of benefits."…”
Section: Resultssupporting
confidence: 66%
“…A high response rate appeared with creativity'. This, in turn, confirms that curiosity triggers creativity [42], while obedience and conformity suppress it. Question seven asked about the skills gained or developed during the course.…”
Section: Resultssupporting
confidence: 66%
“…The results of this research contributed to developing the results of previous research on curiosity [1], [4], [8], [10]- [12]by showing that curiosity is correlated with one's mathematical creativity and also curiosity has a positive effect on students' mathematical creativity. The effect of curiosity on students' mathematical creativity is 43%.…”
Section: Discussionmentioning
confidence: 53%
“…The importance of this curiosity causes various researchers to be interested in exploring further curiosity. Previous research explored the effect of self-efficacy in creativity and curiosity on creative emotions [8]. The results showed that self-efficacy in creativity had an effect of 29.6% on creative emotions and self-efficacy in curiosity had an effect of 17.8% on creative emotions.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, fondness for challenges is defined as the behavioral tendency to seek out a plethora of potential solutions actively, resourcefully explore materials to solve problems, and love mathematical challenges (Grégoire, 2016;Rabi & Masran, 2016). Curiosity is defined as the behavioral tendency to question, engage in novel activities, be interested in mysteries, an attraction to puzzles, and eagerness to embrace novel experiences (Aizikovitsh-Udi & Amit, 2011; Daher et al, 2021;Ennis, 1993;Herwin & Nurhayati, 2021;Kashdan et al, 2018;Suhirman et al, 2021;Tan et al, 2021). Imagination is defined as a behavioral inclination encompassing the capacity to conjure and fashion mental imagery, envision scenarios that transcend existing realities and traverse domains that extend beyond the sensory perception (Jagals & van der Walt, 2019;Kanoknitanunt et al, 2021;Turan & Dişçeken, 2019).…”
mentioning
confidence: 99%